Staying on your feet: the effectiveness of posture and handles in counteracting balance perturbation. Issue 5 (4th May 2019) - Čamernik, Jernej; Azad, Morteza; Peternel, Luka; Potocanac, Zrinka; Babič, Jan
Abstract: Stairways, public transport and inclined walkways are often considered as sites with higher likelihood of falls due to a sudden loss of balance. Such sites are usually marked with warning signs, equipped with non-slip surfaces and handles or handrails to avert or decrease this likelihood. Especially, handles are supposed to provide additional support in cases of a sudden loss of balance. However, the mechanisms of using handles for balance at different heights are not yet fully disclosed. We simulated full body perturbations by applying an anterior force to the waist and investigated effectiveness and mechanisms of balance recovery in five different postures: step stance and normal stance with or without holding handles at different heights. Results indicate that both step stance and holding handles at different vertical positions sufficiently assist balance recovery, compared to normal stance. While there was no significant effect of handle in CoM displacement, the shoulder height handle required the lowest handle force, indicating a difference in using the handle. Practitioner summary: To investigate handle use for balance recovery, we perturbed healthy young adults in different standing positions. Even though the use of different handles had a similar effect, the lowest forces were exerted on the shoulder height handle indicating a preferred handle position for balance recovery. Abbreviation: AP: antero-posterior; CNS: Central nervous system; CoM: Center of Mass; CoMmax: Maximal displacement of the center of mass; CoP: Center of pressure; FHmax: Maximal resultant force exerted on the handle; hFHmax: Maximal horizontal force exerted on the handle; vFHmax; Maximal vertical force exerted on the handle; M1-M8: Perturbation force magnitude